Computer accessibility issues for older adults with disabilities: a pilot study. - Marchant TD; Tiernan TM; Mann WC (OTJR: Occupation, Participation & Health)
The number of adults older than 65 years is expected to increase dramatically during the next 30 years. Older adults have been described as one of the fastest growing groups of computer users, and have been shown to uniquely benefit from computer use. Given their increased susceptibility toward disabling conditions and age-related decline, older adults often face challenges regarding computer use and accessibility. The purpose of this pilot study was to explore computer use and accessibility issues of older adults with disabilities, focusing on relationships between workstation, performance, satisfaction, and self-reported pain. A sample of 32 older adults with disabilities who owned and used a personal computer were interviewed in their homes and observed during performance of a familiar computer task. Their computer workstations were also assessed for adherence to ergonomic principles. Satisfaction with their computer ability was found to be positively correlated with workstation design, their perception of the importance of a computer, duration of use per week, and participants' perception of performance. No significant differences were found between older adults who did and did not report pain associated with computer use. Results suggest that older adults with disabilities are using computers for many tasks, consider their computers important, perceive their performance as relatively good, and are generally satisfied with their ability to use their computer. There is a need for further research examining the correlates of older adults' satisfaction with their ability to use their computer.